Encryption Binary Images by Using Template Matching - Sundus Ebraheem (Al-Rafidain Journal of Computer Sciences and Mathematics)
Text encryption is a very important field in application of data transformation through the digital networks, and the Internet, so it is very necessary to do encryption operation on the text data to get more security in data transformation. In this paper, we present a method -Template Matching- to encrypt data which is represented in form of image with BMP extension by using Mono Digital Images method with partial compression for the data by using RLE method which increases the security of the method and reduces the file size. The application results is efficient for the printed or handwritten text in Arabic or English or any other language, and for the maps or sketches images. The method gives a good ability for data encryption. It is suitable for data transformation through the Internet networks.